Analisis Pengaruh Promosi dan Kualitas Layanan Terhadap Loyalitas Melalui Kepuasan Pelanggan Aplikasi Grab Pada Masyarakat di Kota Semarang (International Forum of Researchers and Lecturers, 2024)
The very rapid development of information and communication technology has brought major changes in various aspects of life, one of which is transportation. In today's digital era, things are made easier for people by the existence of various online transportation services, one of which is Grab. Grab is one of the largest online transportation services in Indonesia, and Grab is very widespread, one of which is in the city of Semarang. Grab offers various transportation services, such as cars, motorbikes, taxis and goods delivery. This research uses quantitative research methods, and the sampling technique uses Non-Probability Sampling. The population in this research is Grab application customers in the city of Semarang. The number of samples taken was 100 respondents. This research uses quantitative analysis techniques. The presentation in this technique is the influence of service quality, level of customer satisfaction and promotion on customer loyalty of the Grab application among people in the city of Semarang. The data obtained in this research was then processed using SmartPLS 3